Sea-level trend variability in the Mediterranean during the 1993–2019 period - Meli, Matteo; Camargo, Carolina M. L.; Olivieri, Marco; Slangen, Aimée B. A.; Romagnoli, Claudia (Frontiers in Marine Science, 2023)
Sea-level change is one of the most concerning climate change and global warming consequences, especially impacting coastal societies and environments. The spatial and temporal variability of sea level is neither linear nor globally uniform, especially in semi-enclosed basins such as the Mediterranean Sea, which is considered a hot spot regarding expected impacts related to climate change. This study investigates sea-level trends and their variability over the Mediterranean Sea from 1993 to 2019. We use gridded sea-level anomaly products from satellite altimetry for the total observed sea level, whereas ocean temperature and salinity profiles from reanalysis were used to compute the thermosteric and halosteric effects, respectively, and the steric component of the sea level. We perform a statistical change point detection to assess the spatial and temporal significance of each trend change. The linear trend provides a clear indication of the non-steric effects as the dominant drivers over the entire period at the Mediterranean Sea scale, except for the Levantine and Aegean sub-basins, where the steric component explains the majority of the sea-level trend. The main changes in sea-level trends are detected around 1997, 2006, 2010, and 2016, associated with Northern Ionian Gyre reversal episodes, which changed the thermohaline properties and water mass redistribution over the sub-basins.